UTILIZING AUDIOVISUAL MEDIA AND LEARNING MOTIVATION ON STUDENT ACHIEVEMENT OF SOCIAL DEPARTMENT GRADE VIII STUDENT FATUMETA, DILI - Agostinho Dos Santos Gonçalves; Virgilio Lopes de Araújo; Sebastião Pereira; Ilidio Ximenes Moreira (International Research-Based Education Journal, 2017)
The purpose of this study was to determine (1) differences effects of using audio-visual media and without audio-visual media to the learning achievement (2) differences effects of high and low motivation on the learning achievement, and (3) learning motivation and interaction effects with and without using audio-visual media on learning achievement. This study was designed by experimental research of using audio-visual media are associated with the learning motivation and it effects on student achievement. To describe the effect on experimental group treated compared with the untreated (control) group. The population of this study were 200 students. This study did not examine the entire population but uses a sample, the two groups. Each group is consisting of 30 students. The instrument that been used is a test to measure the results of social studies and questionnaires to determine the student's learning style. Test and questionnaire was using to collect the data. The data been analysed by ANOVA 2 pathway. Data analysis was carried out using SPSS 22 for windows. Data was analysed to determine learning motivation of each student, and to test the hypotheses that have been formulated. to Keywords: audio-visual media, learning motivation, learning achievement